Cloning and expression of a novel lipase gene from Bacillus sphaericus 205y - Rahman, R.N.Z.A.; Chin, J.H.; Salleh, A.B.; Basri, M. (Springer Verlag, 2003)
A Bacillus sphaericus strain (205y) that produces an organic solvent-tolerant lipase was isolated in Port Dickson, Malaysia. The gene for the lipase was recovered from a genomic library and sequenced. Phylogenetic analysis was performed based on an alignment of thirteen microbial lipase sequences obtained from the NCBI database. The analysis suggested that the B. sphaericus lipase gene is a novel gene, as it is distinct from other lipase genes in Families 1.4 and 1.5 reported so far. Expression in Escherichia coli under the control of the lacZ promoter resulted in an eight-fold increase in enzyme activity after a 3-h induction with 1 mM IPTG. The crude enzyme thus obtained showed a slight (10%) enhancement in activity after a 30-min incubation in 25% (v/v) n -hexane at 37°C, and retained 90% of its activity after a similar period in 25% (v/v) p-xylene.